Environmental education to build school members’ character - Hana Naqiyya Nada; Rhina Uchyani Fajarningsih; Okid Parama Astirin (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Environmental education provides opportunities to instill character education for adolescents in globalization era. However, positive effects of environmental education on character building are rarely studied. This study aimed at analyzing the effect of environmental education on character building of school members. This study used descriptive qualitative method with purposive sampling technique. SJHS 1 Wajak and SJHS 1 Gondanglegi, Malang-East Java were selected as research locations as they were Adiwiyata schools. The data were collected through observation, interview, and documentation techniques. The results showed that environmental education had affected student character building. Various activities and existing regulations affect student characters, such as honest, self-confidence, responsibility, discipline, caring for fellow human beings, caring about nature, courage, religion, and creativity. Habituation and modeling are strategies used in constructing characters. Therefore, environmental education is recommended to be implemented in various schools as an effort to improve the character of school members.